Nanogenerators: 3D Carbon Electrode Based Triboelectric Nanogenerator (Adv. Mater. Technol. 8/2016). Issue 8 (10th November 2016) - Kim, Daewon; Pramanick, Bidhan; Salazar, Arnoldo; Tcho, Il‐Woong; Madou, Marc J.; Jung, Eun Sang; Choi, Yang‐Kyu; Hwang, Hyundoo
Abstract : In article number 1600160, Yang‐Kyu Choi, Hyundoo Hwang, and co‐workers demonstrate a triboelectric nanogenerator (TENG) using a conductive carbon layer as a contact electrode. A patterned photoresist (PR) is converted into a highly conductive carbon design by pyrolysis. Considerable improvement in triboelectric charge induction is attained due to the increased effective contact area for carbon electrodes with micro‐posts and nanofibers.